(untitled) (Journal of Parents and Teachers, 2013)
This article talks about the animations that were done in hospitals with the pediatric patients. The need of doing quality animation activities in hospitals that guarantees its continuity is showed-up. According with this, some indications about the kind of animation activities to do in hospitals are proposed and the benefits that they have (basically), in the pediatric patients, are shaped.